2022
DOI: 10.30762/jeels.v7i1.210
|View full text |Cite
|
Sign up to set email alerts
|

Developing Android-Based English Vocabulary Learning Materials for Primary School Students

Abstract: This study intended to develop an android-based application for English vocabulary learning for primary school students. By implementing Design and Development design model, the researcher underwent three main stages namely; 1) Design, 2) Development, and 3) Evaluation. Through the use of questionnaires and interview guide, the needs were assessed. The results showed that the primary school students need more time to learn English and emphasize more on vocabulary learning. The primary school students need a sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The use of these software was very useful in creating android-based learning application. In line with this, Santosa et al (2020) who stated that technology is very effective to be used in improving the teaching and learning process.…”
Section: Resultsmentioning
confidence: 81%
“…The use of these software was very useful in creating android-based learning application. In line with this, Santosa et al (2020) who stated that technology is very effective to be used in improving the teaching and learning process.…”
Section: Resultsmentioning
confidence: 81%
“…These are to equip the students to take more prominent roles in the global context. Some works from Kivunja (2015), Freitas and Yapp (2005), Piirto (2011), Trilling and Fadel (2009), Santosa (2019), Santosa et al (2019Santosa et al ( , 2020 are a good start to comprehend this current ELT research practice.…”
Section: Changes In Goals Of English Teaching and Learningmentioning
confidence: 99%
“…Students may know more than their teachers about how to use technology, and yet they need proper guidance from the teachers on how to select, analyze, and utilize the right information to achieve their learning goals. Some prominent works on this research field are from Xu et al (2020), Kidd and Morris (2018), Warschauer (1998), Priyanti et al (2019), Banjar et al (2020), Arta et al (2019), Santosa et al (2020).…”
Section: Rapid Development and Integration Of Information Technology ...mentioning
confidence: 99%
“…Likewise, a research conducted by Setiawan & Iasha (2020) showed that WhatsApp became one of top-ranking applications used as learning medium. Mobile phone applications support the teaching and learning process by facilitating students to search information and ideas, enhancing students' motivation (Wang, 2017), enriching vocabulary (Santosa et al, 2020), and promoting students' self-directed learning (Zou & Li, 2015). Later, Fauzi & Khusuma (2020) found that 44% of teachers develop their own media, especially audiovisual media.…”
Section: Introductionmentioning
confidence: 99%